Implementing wireless local area network (WLAN) in United Technology (M) Sdn Bhd - Hari Krishnan, A. (2006)
Wireless becomes part and parcel in today's world. The widespread strategic reliance on networking among competitive businesses and the meteoric growth of the internet and online services are strong testimonies to the benefits of shared data and resources. With wireless LAN, users can access shared information without looking for place to plug in and network managers can set up of augment networks without installing or moving wires. Wireless LANs offers productivity, service, and convenience and cost advantages over traditional wired networks. Thus, this piece of industrial training report is summarizing a complete scenario in setting up a WLAN in United Technology (M) Sdn Bhd under a team of 6 personnel, whereby 1 am one of them. (Author's abstract)